2019
DOI: 10.1177/0261927x19834326
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring Respect: The Effects of Threat to Face on Replies and the Ensuing Questions During Broadcast Political Interviews in Japan

Abstract: This article examines the effect of threat to face to both interviewers and interviewees during live televised interview programs in Japan, where the concept of “face” is of extreme importance in maintaining interpersonal relationships. Based on 2,422 questions identified during 120 interviews broadcast over a period of 12 months on four television programs, the goal is twofold: First, to assess the extent to which questions that contain a certain level of threat to face affect the interviewees’ replies, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The harsh realities of fast-paced changes in conceivably all domains of human activity point in the direction of psychosocial transformations as well. For example, O. Feldman and S. Zmerli argue that media are capable of framing specific aspects of perceived reality as they choose and freely exclude what to report on, including genderbiased news and femininity (Feldman and Zmerli 2019;Feldman and Kinoshita 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The harsh realities of fast-paced changes in conceivably all domains of human activity point in the direction of psychosocial transformations as well. For example, O. Feldman and S. Zmerli argue that media are capable of framing specific aspects of perceived reality as they choose and freely exclude what to report on, including genderbiased news and femininity (Feldman and Zmerli 2019;Feldman and Kinoshita 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Partisan bias and threats against the interviewee are present in various cultures (Gnisci et al, 2013). Even in a context as different from Western cultures as Japan, a study revealed that interviewers' questions affected the interviewees' answers, which in turn altered the journalists' subsequent questions (Feldman & Kinoshita, 2019). In particular, the way that interviewers manage the threat is not reflected in the content of the questions but in the way the questions are asked (Feldman & Kinoshita, 2019).…”
Section: Bias and Threats In Televised Interviewsmentioning
confidence: 99%
“…The next variable used in the study, intensity of questions (Q(n)I), has been determined on the basis of studies by Feldman & Kinoshita (2019) in the field of linguistic research. Our analysis of the interviewees' answers was based on content and context, two of the dimensions considered in equivocation theory (Bavelas et al, 1990), taking into account the modifications suggested in subsequent studies (Feldman et al, 2016).…”
Section: Table 2 Encoding Of Variablesmentioning
confidence: 99%